Impact of Investment on Labour Productivity in Azerbaijan's Chemical and Petrochemical Industry - Vilayat Ismayilov; Nizami Gafarov; Sabina Valiyeva (Qubahan Academic Journal)
The subject of research related to the impact of investment on industrial productivity in Azerbaijan is relevant and essential for understanding the economic situation in the country and for designing effective strategies for the development of the industry. The purpose of this research is to explore the relationship between investment and labour productivity in the sectors of the Azerbaijani economy. The research employed a combination of analytical methods, including statistical analysis of data from the State Statistical Committee of Azerbaijan on labour productivity and investment in the chemical and petrochemical sectors. Functional analysis was used to examine the role of labour productivity, while systematic analysis explored the factors influencing productivity. The research also utilized deduction to establish general principles, synthesis to integrate data, and comparative analysis to identify effective investment areas. The study revealed that investing in the chemical and petrochemical sectors in Azerbaijan has a beneficial effect on labour productivity. Technological innovation, labour skills, working conditions, and infrastructure were identified as factors that impact labour productivity in these industries. Various investment areas that can enhance productivity have been identified, including investments in human capital, production organisation, and advanced technology. The study investigates the direct impacts of investments in technology, human capital, and infrastructure on labour productivity within Azerbaijan's chemical and petrochemical industries and identifies which specific areas of investment most effectively enhance productivity and the underlying reasons for their success. The practical significance of this research lies in utilising the identified findings to tackle issues about enhancing labour productivity in Azerbaijan's economic sectors, thereby elevating this process to a higher level.